Real-time quantification of Pseudomonas fluorescens cell removal from glass surfaces due to bacteriophage FS1 application - Sillankorva, Sanna (2008)
Aims: To study the efficacy of the lytic phage φS1 in eliminating Pseudomonas fluorescens in the early stage of biofilm formation, using an in situ and real time methodology for cell quantification. Methods and Results: Cell adhesion and phage infection studies were carried out in a parallel plate flow chamber under laminar conditions. Cells were allowed to adhere until reaching 1·7–1·8 × 106 cells cm−2 and phage infection was performed with two different phage concentrations (2 × 109 PFU ml−1 and 1 × 1010 PFU ml−1). Phage concentration clearly affects the speed of infection. The less concentrated phage solution promoted a three times slower rate of cell removal but did not affect the overall percentage of cell removal. In fact, after a longer infection period the less concentrated phage solution reached the same 93% cell removal value. Conclusions: Phages are efficient in the eradication of bacterial cells at the early stage of biofilm formation and their presence at the surface did not allow bacterial recolonization of the surface. Significance and Impact of the Study: To date, no published studies have been made concerning in situ and real time quantification of cell removal from surfaces due to phage action.